Radiating pain to the lower extremities caused by lumbar disk rupture without spinal nerve root involvement. - Milette, P C; Fontaine, S; Lepanto, L; Breton, G (American Journal of Neuroradiology, 1995)
PURPOSE To locate the origin of the pain during lumbar diskography by means of a limited intradiskal injection of a local anesthetic. METHODS Lumbar diskography by the direct central posterior approach was performed in 235 consecutive patients. In 17 patients, severe and persistent low back pain, with unilateral or bilateral radiation to the lower extremities, was provoked by contrast injection into only one disk. One milliliter of 1% lidocaine was then slowly injected in the center of these disks. RESULTS A 75% to 100% reduction of the low back pain was experienced by 13 patients, and a 75% to 100% reduction of the radiating pain was experienced by 16 patients within 60 seconds after the intradiskal injection of lidocaine. Radiographs demonstrated radial tears through the entire annulus thickness in 16 of 17 disks. CONCLUSION Our results suggest that, in some patients with low back pain and unilateral or bilateral radiation to the lower extremities, the pain arises from within the disk. In these cases, pain radiating to the lower limb seems to be a referred type and seems unrelated to direct nerve root compression or irritation by a disk fragment in the epidural space.